“Delirium superimposed on dementia is associated with prolonged length of stay and poor outcomes in hospitalized older adults” - Fick, Donna M. (2013)
BACKGROUND: Current literature does not identify the significance of underlying cognitive impairment and delirium on older adults during and 30 days following acute care hospitalization. OBJECTIVE: Describe the incidence, risk factors, and outcomes associated with incident delirium superimposed on dementia. DESIGN: 24-month prospective cohort study SETTING: community hospital PATIENTS: 139 older adults (>65 years) with dementia METHODS: This prospective study followed patients daily during hospitalization and one month post-hospital. Main measures included dementia (Modified Blessed Dementia Rating Score, IQ CODE), daily mental status change, dementia stage/severity (Clinical Dementia Rating, Global Deterioration Scale), delirium (Confusion Assessment Method), and delirium severity (Delirium Rating Scale-Revised-98). All statistical analysis was performed using SAS 9.3 and significance with an alpha level of 0.05. Logistic regression, analysis of covariance or linear regression was performed controlling for age, gender and dementia stage. RESULTS: The overall incidence of new delirium was 32% (44/140). Those with delirium had a 25% short term mortality rate, increased length of stay and poorer function at discharge. At one month follow-up, subjects with delirium had greater functional decline. Males were more likely to develop delirium and for every one unit increase in dementia severity (Global Deterioration Scale), subjects were 1.5 times more likely to develop delirium. CONCLUSIONS: Delirium prolongs hospitalization for persons with dementia. Thus, interventions to increase early detection of delirium have the potential to decrease the severity and duration of delirium and to prevent unnecessary suffering and costs from the complications of delirium and unnecessary readmissions to the hospital.